PENGARUH KOMPETENSI AUDITOR DAN SKEPTISME PROFESIONAL AUDITOR PEMERINTAH TERHADAP KUALITAS LAPORAN HASIL AUDIT PADA PEMERINTAH KOTA LHOKSEUMAWE - Mukhlisul Muzahid (Ekonis: Jurnal Ekonomi dan Bisnis, 2021)
Abstract: This study aims to test empirically the effect of auditor competence and professional skepticism of government auditors on the quality of audit reports on the city government of Lhokseumawe. The analytical tool used is multiple regression analysis with the consideration that the pattern of relationships between variables in the study is correlative and causality. This model will be able to answer the form of the problem, namely measuring how much influence the influence of auditor competence and professional skepticism of government auditors on the quality of audit reports simultaneously or partially at the Lhokseumawe city government. The intended respondents are government auditors who work at the Inspectorate office of Lhokseumawe, totaling 30 respondents, because it is believed that they have the ability to audit government institutions / offices. The data sources used in this study are primary and secondary data with data collection techniques through distributing questionnaires and interviews. The results of this study indicate that simultaneously the competence of auditors and professional skepticism of government auditors have an effect on the quality of audit reports, and partially the competence of auditors and professional skepticism of government auditors have a positive effect on the quality of the audit reports on the financial statements of local government work units of Lhokseumawe City. The results of this study are expected to become a reference and consideration for local governments, especially the auditors of the Lhokseumawe city government, so that the audit implementation prioritizes their professionalism.Keywords: Competence, professional skepticism and quality of audit reports